ANALISIS PERLINDUNGAN DATA PRIBADI DALAM PENGGUNAAN SISTEM LAYANAN INFORMASI KEUANGAN OTORITAS JASA KEUANGAN SEBAGAI ALAT BUKTI PADA PEMBUKTIAN PERMOHONAN PKPU (STUDI PUTUSAN NOMOR 92/Pdt.Sus-PKPU/2023/PN Niaga.Jkt.Pst) - Setyadarma, Ridwan; Hartanto, Heri (Sebelas Maret University, 2025)
This article discusses the legal protection of personal data in the use of SLIK OJK as evidence in the proceedings of PKPU applications submitted by creditors. The purpose of this article is to determine the suitability of the use of SLIK OJK as evidence in the PKPU application and is related to the Law Number 27 of 2022 on the Protection of Personal Data. This article uses a prescriptive and applied normative legal research method with a case study approach. The sources of legal materials used are primary and secondarylegal materials, by means of document studies or library materials, and legal material analysis techniques using syllogism and interpretation using a deductive mindset. Based on the results of research and discussion, it can be seen that further arrangements are needed regarding the procedures for using SLIK data in the PKPU process to maintain a balance between evidentiary efficiency and protection of human rights to personal data.